Wearable and Flexible Ozone Generating System for Treatment of Infected Dermal Wounds - Roth, Alexander; Elkashif, Ahmed; Selvamani, Vidhya; Stucky, Rachel Abigail; Seleem, Mohamed N.; Ziaie, Babak; Rahimi, Rahim (Frontiers in Bioengineering and Biotechnology, 2020)
Wound-associated infections are a significant and rising health concern throughout the world owing to aging population, prevalence of diabetes, and obesity. In addition, the rapid increase of lifethreatening antibiotic resistant infections has resulted in challenging wound complications with limited choices of effective therapeutics. Recently, topical ozone therapy has shown to be a promising alternative approach for treatment of non-healing and infected wounds by providing strong antibacterial properties while stimulating the local tissue repair and regeneration. However, utilization of ozone as a treatment for infected wounds has been challenging thus far due to the need for large equipment usable only in contained, clinical settings. This work reports on the development of a portable topical ozone therapy system comprised of a flexible and disposable semipermeable dressing connected to a portable and reusable ozone-generating unit via a flexible tube. The dressing consists of a multilayered structure with gradient porosities to achieve uniform ozone distribution.The effective bactericidal properties of the ozone delivery platform were confirmed with two of the most commonly pathogenic bacteria found in wound infections, Pseudomonas aeruginosa and Staphylococcus epidermidis. Furthermore, cytotoxicity tests with human fibroblasts and keratinocyte cells indicated no adverse effects on human cells.